PENYIMPANAN SERBUKSARI PISANG LIAR Musa acuminata Colla UNTUK MENDUKUNG PROGRAM PEMULIAAN PISANG BUDIDAYA [Pollen Storage of Wild Varieties of Musa acuminata Colla Ensuring Pollen Source for Cultivated Banana Breeding Program] - Rachman, Erlin; Poerba, Yuyu Suryasari; Ahmad, Fajaruddin (BERITA BIOLOGI, 2012)
Research on pollen storage of four varieties and one subspecies of wild banana, Musa acuminata Colla, was carried out to support genetic improvement of banana cultivars through hybridization. The four wild varieties, breviformis, zebrina, malaccensis, bantamensis and a subspecies banksii cultivated at Cibinong Science Center (CSC-LIPI), Cibinong. Anthers were collected, put on bread paper,dried on hot plate at 40ºC for about two hours, open dried at room temperature in the laboratory (about 26ºC) for overnight, prepared for storage in two ways: -using and, -without silica gel, then stored in three storage temperatures, -5ºC, 5ºC and room temperature. Pollen germination was observed one day before storage, one week, four or five weeks and 12 weeks of storage. At the beginning, M. acuminata ssp banksii had highest pollen germination percentage, followed respectively by varieties bantamensis, breviformis, malaccensis and zebrina. The pollen germination ranks for the five banana varieties were remaining constant up to 12 weeks of storage though pollen germination dynamics occurred week by week. Silica gel may be recommended to be used until 5 weeks of storage. Storage temperature of -5ºC and 5ºC may be recommended as better storage temperature compared to room temperature. No special pattern shown by pollen tube vigor, but subspecies banksii pollen stored without silica gel, at 5ºC and room temperature tends to form better pollen tube vigor than stored at -5ºC.